TINJAUAN TENTANG REKSA DANA KONVENSIONAL DAN REKSA DANA SYARIAH - Ahmad Anto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
Invesment inculcated in the form of reksa fund, its management is marginally divided by for management with the system of Moslem law conventional system and. Knowledge in around reksa fund for wide society of minim still so that enthusiasm for the invesment of in reksa fund even also still not yet maximal. Still very needed by is a effort to increase the understanding of society of about reksa fund, like hitting: advantage / benefit and risk, mechanism work the nya, monitoring result, and others. Is altogether needed to to be used as by a consideration base of before strarting to have invesment